Legislative Protection of Birds of Prey and Strengthening the Fight Against Their Illegal Traffic in Kazakhstan - Sergey L. Sklyarenko (Пернатые хищники и их охрана)
The fauna of birds of prey in Kazakhstan includes 40 species, 15 species are included in the “List of rare and endangered species of animals” (Red Book of the Republic of Kazakhstan). According to the Law “On the Protection, Reproduction and Use of Wildlife” (Article 15), the taking of individuals of rare and endangered species from nature is allowed in exceptional cases by decision of the Government of the Republic of Kazakhstan, for: 1) breeding in specially created conditions for scientific, reproduction, commercial purposes, as well as for subsequent release into the environment; 2) development of national hunting; 3) scientific research; 4) selection. In the last at least 10 years, no permits have been issued for the taken of rare species of birds of prey from nature.